Pengaturan dan Pelaksanaan Praktek Pengadaan Barang/Jasa Pekerjaan Konstruksi Pada Perguruan Tinggi Negeri Badan Hukum - Ajik Sujoko (Administrative Law and Governance Journal, 2022)
Abstract: The PBJ of construction work at PTN Legal Entities is interesting to discuss, so it is the basis for researching several arrangements related to construction work as input in the implementation of construction work. This research is legal research using a statutory approach. The result of the research shows that most of the PBJ in PTN Legal Entities whose funds are sourced from the APBN following Presidential Regulation Number 16 of 2018 and its amendments. Implementation of PBJ whose funds are sourced outside the APBN is guided by the PBJ regulations of each PTN Legal Entities. The PBJ provisions excluded in PTN Legal Entities are related to the PBJ organization and segmentation of the value of construction work, some of which follow the provisions of Presidential Regulation No. 16 of 2018. There are variations or terms for naming sources of funds in PTN Legal Entities originating outside the APBN/APBD. The form of a construction work contract consists of an Order, a Work Start Order (SPMK), a Work Order (SPK), a Letter of Agreement. Several PBJ regulations at PTN Legal Entities have not regulated the segmentation of construction work packages for business qualifications. Several PBJ regulations at PTN Legal Entities have not explained the qualifications of businesses that will carry out KSO in construction work. The scale of the application of blacklist sanctions at PTN Legal Entities for providers is 2, namely the national scale and the internal scale of PTN Legal Entities. Keywords: PTN Legal Entities, construction work  Abstrak: PBJ pekerjaan konstruksi di PTN Badan Hukum menarik untuk dibahas, sehingga mendasari untuk meneliti beberapa pengaturan terkait pekerjaan konstruksi sebagai masukan dalam pelaksanaan pekerjaan konstruksi. Penelitian ini merupakan penelitian hukum (legal research) dengan menggunakan pendekatan peraturan perundang-undangan (statutory approach). Hasil penelitian bahwa sebagian besar PBJ di PTN-Badan Hukum dananya bersumber dari APBN mengikuti Perpres Nomor 16 Tahun 2018 dan perubahannya. Pelaksanaan PBJ yang dananya bersumber di luar APBN berpedoman pada peraturan PBJ masing-masing PTN Badan Hukum. Ketentuan PBJ dikecualikan di PTN Badan Hukum terkait dengan organisasi PBJ dan segmentasi nilai pekerjaan konstruksi ada yang sebagian dan ada yang seluruhnya mengikuti ketentuan Perpres Nomor 16 Tahun 2018. Ada variasi atau istilah penamanaan sumber dana di PTN Badan Hukum yang bersumber di luar APBN/APBD. Bentuk kontrak pekerjaan konstruksi terdiri Surat Pesanan, Surat Perintah Mulai Kerja (SPMK), Surat Perintah Kerja (SPK) dan Surat Perjanjian. Beberapa peraturan PBJ di PTN Badan Hukum belum mengatur segmentasi paket pekerjaan konstruksi untuk kualifikasi usaha. Beberapa peraturan PBJ di PTN Badan Hukum belum menjelaskan kualifikasi usaha yang akan melakukan KSO pada pekerjaan konstruksi. Skala pemberlakuan sanksi daftar hitam di PTN Badan Hukum bagi penyedia ada 2 yaitu skala nasional dan skala Internal PTN Badan Hukum. Kata Kunci: PTN Badan Hukum, pekerjaan konstruksi